OPTIMIZATION OF BIOGAS PRODUCTION FROM TOFU WASTEWATER - Purwanti, Ani; Muchlis, Muchlis; Arbintarso, Ellyawan Setyo; Rahayu, Suparni Setyowati; Gusmarwani, Sri Rahayu; Pangestu, Muhammad Puri Dwi; Prayogo, Wisnu (Directorate of Research and Community Service (DRPM), 2022)
The Seyegan tofu industry has increased the output of tofu wastewater, which has not yet been put to good use. Biogas can be created by mixing wastewater from the tofu business with waste from the cow feces industry. In this study, we measure the time of fermentation, the composition variation, and the rate of increase in gas pressure from the biogas generation process. Three versions with three repetitions each were used in this investigation. Three different variations were tested: one with a ratio of 20% cow excrement and 80% wastewater tofu industry, one with a ratio of 35% cow feces and 65% wastewater tofu industry, and one with a ratio of 50% cow feces and 50% wastewater tofu industry. Using a biogas reactor consisting of 120 L plastic drums, the experiment was conducted. Gas pressure (mm) was monitored with a water column and fermentation duration using a digital timer (hours). To ascertain the viscosity variance of each variation composition, a level test was conducted. By using the gravimetric approach, water. According to the study's findings, a 2.5 mm water column containing a mixture of 50% cow feces and 50% wastewater from the tofu business had the maximum gas pressure. The ideal ratio of mixed materials within 7 days has a significant impact on optimal biogas production.